Historicity Muhammadiyah: What was the Idea of the Founder of Muhammadiyah as a â€œProgressive Islamic Movement?â€ - Darmayanti, Rani; Nurhakim, Moh.; Utsman, Yusuf Olawale Owa-Onire; Amien, Syaiful (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
This research aims to examine the historicity of KH Ahmad Dahlan, founder of Muhammadiyah, in emphasizing the theological principles of tajwid and ijtihad, describing the concept of development used by KH Ahmad Dahlan as an intellectual reaction to the social, political and economic challenges faced by Indonesian society during the Dutch colonial rule. This research uses systematic literature observation (SLR) methodology to identify, disseminate, and analyze all relevant research to answer research questions using the 7P technique. This research increases scientific knowledge about the Islamic reform movement, how insight into the theological principles it offers especially in the modern era, and how the concept of